Biopolymer- and Lipid-Based Carriers for the Delivery of Plant-Based Ingredients - Lynda Gali; Annachiara Pirozzi; Francesco Donsì (MDPI AG, 2023)
Natural ingredients are gaining increasing attention from manufacturers following consumers' concerns about the excessive use of synthetic ingredients. However, the use of natural extracts or molecules to achieve desirable qualities throughout the shelf life of foodstuff and, upon consumption, in the relevant biological environment is severely limited by their poor performance, especially with respect to solubility, stability against environmental conditions during product manufacturing, storage, and bioavailability upon consumption. Nanoencapsulation can be seen as an attractive approach with which to overcome these challenges. Among the different nanoencapsulation systems, lipids and biopolymer-based nanocarriers have emerged as the most effective ones because of their intrinsic low toxicity following their formulation with biocompatible and biodegradable materials. The present review aims to provide a survey of the recent advances in nanoscale carriers, formulated with biopolymers or lipids, for the encapsulation of natural compounds and plant extracts.